1987
DOI: 10.1161/01.res.60.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-dependent relaxation in experimental atherosclerosis in the rabbit.

Abstract: The effect of feeding a diet supplemented with lipids and containing 2% cholesterol on the endothelium-dependent relaxation of rabbit aorta to acetylcholine was assessed. The effect of feeding a standard rabbit diet after an initial period of 2% cholesterol feeding was assessed also. Age-matched male, New Zealand white rabbits were fed either a 2% cholesterol diet or a standard rabbit diet. The animals were-anesthetized with pentobarbitone sodium (25 mg/kg) and killed either at the beginning of the study (0 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
3

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(61 citation statements)
references
References 23 publications
6
52
0
3
Order By: Relevance
“…It has been reported earlier that endothelial function may be abnormal within a few hours of exposure to increased levels of LDL cholesterol (16,32,40). Thus, vascular reactivity was expected to change in the presence of high levels of LDL cholesterol, especially in the female offspring.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been reported earlier that endothelial function may be abnormal within a few hours of exposure to increased levels of LDL cholesterol (16,32,40). Thus, vascular reactivity was expected to change in the presence of high levels of LDL cholesterol, especially in the female offspring.…”
Section: Discussionmentioning
confidence: 95%
“…SFA intake raises plasma LDL levels (54,60) and inhibits the expression of hepatic LDL-receptor (LDL-r) (29,31). Both in vitro and in vivo studies have shown that aortic endothelial function may be abnormal within a few hours of exposure to increased levels of LDL cholesterol (32,40). Furthermore, SFA intake can evoke free radical synthesis that may contribute to vascular dysfunction by decreasing endothelium-derived vasodilator molecules like nitric oxide (NO) (20).…”
mentioning
confidence: 99%
“…In spite of the deliberate inclusion of rabbits without hypercholesterolaemia, the modest desensitization to the a,-adrenoceptor agonist, phenylephrine (Habib et al, 1986;Mugge et al, 1991), the increased sensitivity and contractility to 5-HT (Henry & Yokoyama, 1980;Verbeuren et al, 1986b;Wines et al, 1989) and the diminished ACh-induced relaxations (Verbeuren et al, 1986b;Freiman et al, 1986;Habib et al, 1986;Jayakody et al, 1987;Bossaller et al, 1987) confirmed the altered reactivity of arteries with fatty streaks.…”
Section: Fatty Streaks and Vascular Reactivitymentioning
confidence: 97%
“…As these experimental 'atherosclerotic lesions' develop, endothelium-dependent relaxations (Verbeuren et al, 1986b;Freiman et al, 1986;Bossaller et al, 1987;Jayakody et al, 1987;Minor et al, 1990) and NO release (Moncada et al, 1991), assessed by bioassay of the 'overflow' of NO into the lumen of the vessel (Guerra et al, 1989;Verbeuren et al, 1990;Minor et al, 1990), become progressively suppressed. The NO defect is presumably the result, rather than the cause of the vascular lesions, since endothelium-dependent responses are preserved in adjacent normal areas and arteries which do not develop fatty streaks (Verbeuren et al, 1986b;Senaratne et al, 1991;Galle et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made to clarify this hyperresponsiveness of arteriosclerotic vessels by experiments in vitro, but the results differed greatly depending on species and experimental conditions (Henry & Yokoyama, 1980;Godfraind & Miller, 1983;Kawachi et al, 1984;j / Ginsburg et al, 1984;Harrison et al, 1987). The defective endothelium-derived relaxing factor (EDRF) release in atherosclerotic vessels (Freiman et al, 1986;Jayakody et al, 1987a; (EDCF) or endothelin (Yanagisawa et al, 1988) as is found in hypertension or in regenerating endothelium (Luescher & Vanhoutte, 1986;Vanhoutte, 1987;Shimokawa et al, 1987 (Hof et al, 1987), for this purpose. The calcium after (continuous line) antagonist shifted the dose-response curves to NA cg 1. n = 6 for each and Phen (but not AII) more effectively to the right in atherosclerotic animals so that the pressor In summary, our experiments support the view that pressor effects of several vasoconstrictor agents are enhanced in atherosclerotic animals.…”
Section: Conscious Rabbitsmentioning
confidence: 99%